2008
DOI: 10.1002/pmic.200700701
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variations of the postnatal rat urinary proteome as a reflection of systemic maturation

Abstract: The rat kidney matures during the first 2 wk of life, suggesting that temporal variations in the urinary proteome may occur during this period. We describe the urine proteome during postnatal development in the rat and demonstrate specific proteomic changes corresponding to developmental milestones. Urine was collected from 30 rats at five postnatal (P) days of life (P1, P3, P7, P14, and >P30) by bladder aspiration. The proteome was assessed by nano-ESI-LC-MS/MS. For identification, we used stringent criteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Normal variations are most likely due to diet, hydration, circadian rhythm, metabolic and catabolic processes, exercise, sex, disease and other environmental factors. Previous work on normal rat urine demonstrated that the urinary proteome undergoes significant changes from birth (0 days) to adulthood (> 30 days) [9]. During days 0 to 14 of life in the rat, proteins associated with cell proliferation and differentiation, cell adhesion, and tissue remodeling were prominent in the urine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal variations are most likely due to diet, hydration, circadian rhythm, metabolic and catabolic processes, exercise, sex, disease and other environmental factors. Previous work on normal rat urine demonstrated that the urinary proteome undergoes significant changes from birth (0 days) to adulthood (> 30 days) [9]. During days 0 to 14 of life in the rat, proteins associated with cell proliferation and differentiation, cell adhesion, and tissue remodeling were prominent in the urine.…”
Section: Resultsmentioning
confidence: 99%
“…To date, there have been no studies that determine if the pediatric urinary proteome is distinct from the adult urinary proteome. In rodents, we previously demonstrated that the urinary proteome changes drastically with normal postnatal maturation [9]. In this study we perform an in-depth analysis of the normal male infant urinary proteome and then compare it to normal healthy adult males and the current reported literature.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, a number of human urinary proteins that increase with normal aging are also those associated with progressive renal disease [108]. In the rat, urinary proteins are found to change during postnatal maturation: 14 proteins involved with cellular adhesion, structure, or proliferation and differentiation are excreted only during neonatal development, while 30 proteins are specific to adults [109].…”
Section: Potential Biomarkers Of Severity and Progression Of Obstructmentioning
confidence: 99%
“…Lee et al used SDS-PAGE and nano-ESI-LC-MS/MS techniques to demonstrate the temporal variations in the urinary proteome during postnatal maturation in the rat 33 . They noted dramatic changes in the normal postnatal urinary proteome secondary to physiologic changes related to nephrogenesis and developmental maturation, and documented a set of proteins as potential markers of normal development 33 . This preliminary work may provide critical insight into renal development and allow for future comparative studies in rat animal models of urologic disease.…”
Section: Proteomics and Urologymentioning
confidence: 99%